Pengaruh Kualitas Produk dan Brand Ambasador Terhadap Keputusan Pembelian Melalui Kepuasan Harga pada Mie Lemonilo - Mitasari, Eliam Lola; Tuti, Meylani (Indonesian Journal Publisher, 2024)
The purpose of this study was to determine the effect of product quality and brand ambassadors on consumer purchasing choices by testing their satisfaction with the price of Lemonilo noodles. The methodology used was Accidental Sampling, with a sample size of 150 respondents. The validity and reliability of the questionnaire given to respondents were tested using PLS software version 3.0 and Structural Equation Modeling (SEM). In the data collection approach, two things are emphasized in the service marketing mix: product quality and brand ambassadors. This study shows that the quality of a product has a large and positive impact on consumer purchasing choices. In addition, it has a positive effect on their satisfaction with the price of the product. Conversely, the presence of a brand ambassador does not have a significant effect on price satisfaction. However, it has a significant effect on consumer purchasing decisions. Furthermore, satisfaction with the price of a product has a positive and significant effect on consumer purchasing choices